The Effect Of Pricing Strategy On Customer Satisfaction In Conditional Buffet Business Kitchen Bar Bar By Kak Mir East Aceh - Dilla Nazatul Amira; Lisa Iryani; Maisyura Maisyura; Sufi Sufi; Teuku Zulkarnaen (Indonesian Journal Economic Review (IJER), 2026)
Competition in the culinary business requires business actors to implement appropriate pricing strategies to increase customer satisfaction. This study aims to determine the effect of pricing strategies on customer satisfaction at the conditional buffet business Dapur Bar Bar by Kak Mir, East Aceh. Conditional buffet businesses are culinary businesses that implement a buffet system with certain conditions, such as price options based on presentation methods and limitations in choosing menus. This study uses a quantitative approach with a descriptive type. The population in this study were customers of Dapur Bar Bar by Kak Mir with a sample of 100 respondents obtained using a purposive sampling technique. Data were collected through a questionnaire with a Likert scale and analyzed using the SPSS program version 25. The results showed that pricing strategies have a positive and significant effect on customer satisfaction. This is evidenced by the calculated t value of 8.848> t table 1.984 and a significance value of 0.000 (<0.05). Meanwhile, the coefficient of determination (R²) value of 0.444 indicates that pricing strategies are able to explain 44.4% of customer satisfaction, while the remaining 55.6% is influenced by other factors outside the study. These findings indicate that the application of affordable prices, in accordance with product quality, the benefits obtained, and competitiveness can support the creation of customer satisfaction in conditional buffet businesses.